PENGARUH PUPUK DAUN DAN NAUNGAN TERHADAP PERTUMBUHAN BIBIT GAHARU Gyrinops verstegii (Gilg) Domke DI BAWAH CEKAMAN AIR. - Anggreine H. Mentang; Johan A. Rombang; Marthen T. Lasut; Alfonsius Thomas (COCOS, 2016)
ABSTRAKThis research aims to know the influence of leaf fertilizers and shade on the growth ofGyrinops verstegii (Gilg) Domke under water stress. This research was conducted in the greenhouse of Faculty of Agriculture, University of Sam Ratulangi Manado, from June to August2013. Spit plot design is used in this research. Shade as main plot consists of two levels,namely: 1 layer of paranet N1 (light intensity Â± 40%) and 2 layers of paranet N2 (lightintensity Â± 16%). Doses of fertilizer as sub-plot consists of 3 levels: P0 as a control (nofertilizer), P1 0.012 g/plant and P2 0.024 g/plant. The fertilizer was given every week for 2months. The effects of both shading and fertilizer treatments were not significant on plantheight and stem diameter under water stress.Keywords: Gyrinops verstegii, water stress.